Legal Protection For Foreign Climbers in Mountain Conservation Areas: A Comparative Study of Indonesia and Several Countries - Listiana, Novy (Fakultas Syariah UIN Antasari, 2025)
The case of the death of a foreign tourist from Brazil on Mount Rinjani Indonesia is a concern considering that the mountain that is a tourist destination is a Conservation Area. Indonesian citizens and Brazilian citizens give each other opinions regarding the security provided by the Indonesian Government to protect foreign tourists. This study analyzes and compares how the legal protection framework for foreign climbers in Indonesia's mountainous conservation areas with several other countries. The main objective is to identify best practices and recommend things that are considered necessary in Indonesia. The research method used was normative research with a comparative legal approach, by choosing Mount Rinjani in Indonesia as the main case study, Mount Kinabalu (Malaysia), Mount Fuji (Japan), and Mount Cook (New Zealand) as comparisons. The results of the study show that although Indonesia has an indirect legal basis that can be used as legal protection for foreign citizen climbers, the provisions of guide and insurance obligations in Indonesia have not been integrated, to show a more proactive approach in risk mitigation and financial handling of accidents. This study recommends the refinement of guide regulations and a clearer role of insurance to improve the legal protection of foreign climbers in Indonesia.